Sosialisasi dan Demonstrasi Pembuatan VCO oleh KKN UNP untuk UMKM Sijantang Koto - Yummi Meirafoni; Susilawati Susilawati; Tifanny Dewi Arimbi; Ismah Hafizah Rasyidah; Muhammad Regio; Putri Alifia Ramadhani (Jurnal Imiah Pengabdian Pada Masyarakat (JIPM), 2025)
Indonesia is one of the world's largest coconut producers, but still faces challenges in the efficient and sustainable production of Virgin Coconut Oil (VCO), especially in rural areas. Limited public knowledge about the environmentally friendly and economically valuable VCO production process is a major obstacle. In response, students from the Community Service Program (KKN) conducted a socialization activity and a simple demonstration of VCO production in Sijantang Koto Village, Sawahlunto City. This activity aims to increase public understanding of the health benefits and economic potential of VCO, as well as encourage responsible production practices. VCO is produced without high heat or chemicals, so that natural ingredients such as healthy fatty acids, vitamin E, and antioxidants are maintained. The simple manufacturing process allows communities to produce VCO independently with easily accessible equipment. This program aligns with Sustainable Development Goal (SDGs) point 12 on responsible consumption and production and has the potential to support the development of locally resource-based MSMEs.